Case report: NUT carcinoma with MXI1::NUTM1 fusion characterized by abdominopelvic lesions and ovarian masses in a middle-aged female - Jiang, Huahua; Wang, Chao; Hou, Zheng; Wang, Yuxiang; Qiao, Jie; Li, Huajun (Frontiers in Oncology, 2023)
Background: Nuclear protein of the testis (NUT) carcinoma is a rare subset of poorly differentiated, highly aggressive malignancy defined by NUTM1 gene rearrangements. Only three NUT cases of probable ovarian origin have been reported. Case presentation: We report a case of NUT carcinoma in a 53-year-old female who presented with extensive abdominopelvic lesions and bilateral ovarian masses suggestive of advanced ovarian cancer. This patient was admitted to our hospital due to abdominal pain and distension for over two months. Imaging examinations suggested a possible malignancy of bilateral adnexal origin. This patient first underwent diagnostic laparoscopy. After receiving neoadjuvant chemotherapy, she underwent cytoreductive surgery. Surgical pathology showed infiltration of monotonous round tumor cells with no apparent differentiation characteristics. Immunohistochemistry (IHC) revealed nuclear expression of the NUT protein. And MXI1::NUTM1 fusion was identified by next-generation sequencing (NGS). Herein, we introduce an unusual NUT carcinoma and describe the clinical, imaging, and pathological features. In addition, we briefly reviewed the published literature and discussed the possibility of primary gynecological NUT carcinoma. Conclusions: Identifying a NUT carcinoma arising from the abdominopelvic cavity is essential, and we underscore the need for NUT testing in undifferentiated malignant neoplasms that appear in this clinical setting. Although it is unclear from which origin this tumor arose, proper classification is essential for treatment planning. Keywords: Case report, NUT carcinoma, NUT rearrangement, Ovarian neoplasms, Undifferentiated pelvic neoplasms.